Toughening modifier for polyester and preparation method thereof

By using toughening modifiers prepared by chlorinated polyethylene and glycidyl methacrylate in polyester materials, the problem of high brittleness of polyester materials at high temperatures is solved, and the efficient increase of polyester materials is achieved Toughness and thermal stability.

CN119431992AActive Publication Date: 2025-02-14SHANDONG RIKE CHEM
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411577551.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

During the processing process, polyester materials have problems such as high brittleness and insufficient thermal decomposition temperature, which causes toughening modifiers to decompose and release harmful gases at high temperatures, damaging the equipment and reducing performance.

Method used

Chlorinated polyethylene is used as the toughening modifier, by controlling the chlorine content between 8 and 25 wt%, the glass transition temperature is <-20°C and the residual crystallinity is 0≤15%, combined with glycidyl methacrylate as Compatible agent to improve the thermal stability and compatibility of toughening modifiers.

Benefits of technology

The good dispersion and toughening effect of toughening modifier in polyester materials is achieved, the processing and forming effect and impact toughness of polyester resin are improved, and the requirements of the high-temperature processing technology of polyester materials are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005122165570000021
    Figure BDA0005122165570000021
  • Figure BDA0005122165570000041
    Figure BDA0005122165570000041
  • Figure BDA0005122165570000111
    Figure BDA0005122165570000111
Patent Text Reader

Abstract

The invention relates to a toughening modifier for polyester and a preparation method of the toughening modifier. The toughening modifier comprises the following components in parts by weight: 85.0-97.2 parts of chlorinated polyethylene, 0.8-5.0 parts of a compatilizer, 0.01-0.2 part of an initiator, 0.5-6.0 parts of filler and a stabilizer, wherein the chlorine content of the chlorinated polyethylene is 8-25%, the glass transition temperature is less than-20 DEG C, and the residual crystallinity is greater than or equal to 0 and less than 15%; the thermal decomposition temperature of the toughening modifier is higher than 200 DEG C. The invention also provides a modified polyester modified by the toughening modifier and a modification method thereof. The toughening modifier has good thermal stability, and can improve the processing molding effect and impact toughness of the polyester resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of toughening agents, and in particular to a toughening modifier for polyester and a preparation method thereof. Background Art

[0002] Polyester material is a kind of thermoplastic engineering plastic, including polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene terephthalate-1,4-cyclohexanedimethanol (PETG) and other materials. Polyester material has good mechanical properties, weather resistance, wear resistance, electrical insulation, chemical resistance and other characteristics, and is widely used in fiber, film, beverage bottles and packaging.

[0003] Due to the excellent properties of polyester materials and the reasonable price, after years of development, China has formed a polyester material production capacity of more than 70 million tons. Its main application field is the fiber field, which is what we often call polyester materials, followed by bottle flakes and packaging fields. The continuous expansion of polyester material production capacity and the abandonment of clothing, beverage bottles and packaging materials have caused a large amount of idle production capacity and waste plastic pollution. The development of new application fields for polyester materials is becoming an urgent problem that needs to be solved by the polyester industry and environmental protection.

[0004] At present, the domestic SPC floor and carbon crystal board market is developing rapidly. It is mainly made of polyvinyl chloride and calcium powder through extrusion and shaping to make stone plastic floor, which replaces the laminate floor and artificial decorative panel on the market. It has the advantages of low cost, no formaldehyde, no odor, easy maintenance, etc. It is widely used in the field of interior decoration and exported to Europe and the United States in large quantities. However, this product also has the disadvantages of short replacement cycle, low recycling value and long degradation cycle, which is restricted by environmental protection requirements. Polyester materials are easy to hydrolyze, have short degradation cycle, high strength and wide material sources. It is an ideal material to replace SPC floor. It not only improves the performance of floor and wall decorative panels, but also realizes the effective utilization of polyester production capacity.

[0005] Floor and wall decoration materials have high requirements for the dimensional stability of products. In order to obtain excellent dimensional stability, a large amount of inorganic fillers need to be added to the products, which will aggravate the disadvantages of polyester materials, such as difficulty in processing and molding and high brittleness. The problem of high brittleness of PET and PETG materials can be solved by developing toughening modifier products with good compatibility with polyester materials, good thermal stability and high impact toughness. Compared with POE, EBA and maleic anhydride grafted polymers, chlorinated polyethylene has obvious price advantages, but the thermal decomposition temperature of traditional chlorinated polyethylene products is around 165°C, and the processing temperature of polyester materials must be above 200°C. Under this processing condition, chlorinated polyethylene will decompose and release hydrogen chloride gas when heated, which will reduce performance and cause equipment corrosion. Therefore, traditional chlorinated polyethylene products cannot be used in the field of polyester material toughening. Summary of the invention

[0006] The purpose of the present application is to provide a toughening modifier for polyester, which can adapt to the higher processing temperature requirements of polyester materials, can be well dispersed in polyester materials and provide excellent toughening effects, thereby solving the problems of high brittleness of existing polyester materials.

[0007] To achieve one aspect of the above-mentioned invention object, the present invention adopts the following technical solution:

[0008] A toughening modifier for polyester is prepared by using raw materials containing the following components in parts by weight:

[0009]

[0010] The chlorinated polyethylene has a chlorine content of 8 to 25 wt%, a glass transition temperature of <-20°C, and a residual crystallinity of 0≤<15%;

[0011] The residual crystallinity is determined by the heat of fusion measured by differential scanning calorimetry according to the national standard GB / T 19466.3-2004 and calculated by the following formula:

[0012] Residual crystallinity = fusion heat of chlorinated polyethylene / theoretical fusion heat of HDPE with 100% crystallinity;

[0013] The thermal decomposition temperature of the toughening modifier is greater than 200°C;

[0014] Preferably, the chlorine content of the chlorinated polyethylene is 8-18 wt %, and the thermal decomposition temperature of the toughening modifier is greater than 245°C.

[0015] In a preferred embodiment, the compatibilizer is glycidyl methacrylate (GMA).

[0016] To achieve another aspect of the above-mentioned object of the invention, the present invention also provides a method for preparing the above-mentioned toughening modifier, comprising the following steps:

[0017] Step 1): adding 0.05-0.5 parts by weight of a dispersant and 0.005-0.06 parts by weight of an emulsifier to a reactor, then adding water to make the total weight of the dispersant, the emulsifier and the water 150 parts by weight, then adding 20-30 parts by weight of high-density polyethylene, introducing an inactive gas from the bottom of the reactor to remove oxygen in the reaction liquid and the gas phase at the top of the reactor, heating the reaction mass to 80-105° C. under stirring, beginning to introduce 3.5-20 parts by weight of chlorine, and simultaneously raising the temperature to 120-140° C., after the chlorine is introduced, cooling to below 100° C., deacidification, neutralization, water washing, centrifugation, and drying to obtain chlorinated polyethylene with a chlorine content of 8-25wt%, a glass transition temperature of less than -20° C., and a residual crystallinity of 0≤less than 15%;

[0018] Step 2): weigh 85.0-97.2 parts by weight of chlorinated polyethylene, 0.8-5.0 parts by weight of a compatibilizer, 0.01-0.2 parts by weight of an initiator, 0.5-6.0 parts by weight of a filler, and 0.5-4.0 parts by weight of a stabilizer, put them into a mixer, stir and mix for 2-5 minutes, and discharge the materials for later use;

[0019] Step 3): The mixed material is extruded and granulated through a twin-screw extruder to obtain the toughening modifier.

[0020] To achieve another aspect of the above object of the invention, the present invention also provides a modified polyester, wherein the modified polyester is a polyester modified by using the above toughening modifier.

[0021] To achieve another aspect of the above-mentioned object of the invention, the present invention further provides a method for preparing the modified polyester.

[0022] Compared with the prior art, this application has the following beneficial effects:

[0023] (1) The toughening modifier of the present application has high thermal stability. The toughening modifier is prepared by combining a chlorinated polyethylene material with a glass transition temperature of less than -20°C, a residual crystallinity of 0≤less than 15%, and a chlorine content of 8 to 25 wt% with other components. The obtained modifier has a good toughening effect on polyester and can improve the processing and molding effect and impact toughness of polyester resin.

[0024] (2) Preferably, the present application also improves the compatibility of the toughening modifier with the polyester material without affecting the heat stability of the toughening modifier by grafting glycidyl methacrylate onto the chlorinated polyethylene material, promotes the dispersion of the toughening modifier in the polyester material, and gives full play to its toughening modification effect.

[0025] (3) Preferably, in the preparation process of chlorinated polyethylene, before introducing chlorine, an inert gas is injected into the reactor to continuously replace the oxygen in the reaction liquid and the gas phase on the liquid surface of the reactor, thereby reducing the oxygen content in the system and reducing the oxidation of high-density polyethylene during the chlorination process, which can effectively improve the heat resistance and stability of chlorinated polyethylene products and meet the high-temperature processing requirements of polyester materials. DETAILED DESCRIPTION

[0026] Typical implementations that embody the features and advantages of the technical solution of the present application will be described in detail in the following description. It should be understood that the present invention can have various changes in different implementations without departing from the scope of the present application, and the descriptions therein are essentially used for illustration rather than for limiting the present invention.

[0027] The "parts" and "%" used in the present application to express the content are all by weight unless otherwise specified. It should be particularly understood that the present invention is not limited to these examples.

[0028] In a first aspect, the present application provides a toughening modifier for polyester, which is prepared by raw materials comprising the following components in parts by weight:

[0029]

[0030] The chlorinated polyethylene has a chlorine content of 8 to 25 wt%, a glass transition temperature of <-20°C, and a residual crystallinity of 0≤<15%;

[0031] The residual crystallinity is determined by the heat of fusion measured by differential scanning calorimetry according to the national standard GB / T 19466.3-2004 and calculated by the following formula:

[0032] Residual crystallinity = melting heat of chlorinated polyethylene / theoretical melting heat of high-density polyethylene (HDPE) with 100% crystallinity;

[0033] The thermal decomposition temperature of the toughening modifier is greater than 200°C.

[0034] Polyester materials belong to crystalline engineering plastics with high melting points, so the processing temperature of polyester materials is high, and general toughening modifiers cannot meet the requirements at this processing temperature. For toughening modifiers, such as chlorinated polyethylene, there is a significant cost advantage, but the thermal decomposition temperature of traditional chlorinated polyethylene products is only about 165°C, and high temperature is easy to decompose, resulting in poor toughening effect and even equipment corrosion. Obviously, traditional chlorinated polyethylene products cannot meet the higher processing temperature requirements when processing polyester materials. For example, the processing temperature of PETG is usually above 200°C. The inventors found that as the chlorine content in chlorinated polyethylene products decreases, the heat resistance stability of the product is improved, and the glass transition temperature of the product is reduced. A low glass transition temperature can provide better toughness, but as the chlorine content of chlorinated polyethylene materials decreases, the residual crystallinity increases, resulting in a decrease in compatibility with polyester materials, thereby reducing the modification effect of the product. The present application uses a chlorinated polyethylene material with a good balance of properties such as glass transition temperature and residual crystallinity to obtain a toughening modifier with good toughening effect and high thermal stability, which can improve the processing and molding effect and impact toughness of polyester resins.

[0035] In a preferred embodiment, the thermal decomposition temperature of the toughening modifier is greater than 245° C., and the chlorine content of the chlorinated polyethylene is 8 to 18 wt %.

[0036] In one embodiment, the compatibilizer is glycidyl methacrylate (GMA). By grafting GMA onto chlorinated polyethylene, the compatibility of the toughening modifier with the polyester material can be improved, and uniform dispersion in the polyester material can be achieved. The compatibility of the toughening modifier with the polyester material is improved without affecting the heat stability of the toughening modifier, and the dispersion of the toughening modifier in the polyester material is promoted to give full play to its toughening modification effect.

[0037] In one embodiment, the initiator is selected from one or more of dicumyl peroxide (DCP), di-tert-butyl cumyl peroxide (BIBP), benzoyl peroxide (BPO), and diisopropylbenzene hydroperoxide (DIP). By selecting a preferred initiator, the grafting rate can be appropriately increased.

[0038] In one embodiment, the filler is selected from one or more of calcium carbonate, talc, titanium dioxide, calcium oxide, and silicon dioxide. By adding fillers, preferably inorganic fillers, adhesion of the toughening modifier finished product can be avoided, which is beneficial to the subsequent mixing process of the toughening modifier and the polyester material and improves the uniformity of the mixing.

[0039] In one embodiment, the stabilizer is one or more of an organic tin stabilizer, a calcium zinc composite stabilizer, a lead salt composite stabilizer, hydrotalcite, and a zeolite. The present application can further improve the thermal stability of the toughening modifier by adding a stabilizer component to the toughening modifier to meet the higher processing temperature requirements of the polyester material.

[0040] In a second aspect, the present invention also provides a method for preparing the above-mentioned toughening modifier, comprising the following steps:

[0041] Step 1): adding 0.05-0.5 parts by weight of a dispersant and 0.005-0.06 parts by weight of an emulsifier to a reactor, then adding water to make the total weight of the dispersant, the emulsifier and the water 150 parts by weight, then adding 20-30 parts by weight of high-density polyethylene, introducing an inactive gas from the bottom of the reactor to remove oxygen in the reaction liquid and the gas phase at the top of the reactor, heating the reaction mass to 80-105° C. under stirring, beginning to introduce 3.5-20 parts by weight of chlorine, and slowly heating to 120-140° C., after the chlorine is introduced, cooling to below 100° C., deacidification, neutralization, water washing, centrifugation, and drying to obtain chlorinated polyethylene with a chlorine content of 8-25wt%, a glass transition temperature of less than -20° C., and a residual crystallinity of 0≤less than 15%;

[0042] Step 2): weigh 85.0-97.2 parts by weight of chlorinated polyethylene, 0.8-5.0 parts by weight of a compatibilizer, 0.01-0.2 parts by weight of an initiator, 0.5-6.0 parts by weight of a filler, and 0.5-4.0 parts by weight of a stabilizer, put them into a mixer, stir and mix for 2-5 minutes, and discharge the materials for later use;

[0043] Step 3): The mixed material is extruded and granulated through a twin-screw extruder to obtain the toughening modifier.

[0044] In the preparation process of chlorinated polyethylene, the present application improves the chlorination uniformity by increasing the initial chlorination temperature, reduces the glass transition temperature of the material and reduces the residual crystallinity, thereby improving the toughening modification effect of the toughening modifier. The inventors also found that in the preparation process of chlorinated polyethylene, when the chlorination reaction temperature is above 100°C, the oxygen in the reactor will oxidize the chlorinated polyethylene material and reduce its heat resistance stability. As the oxygen content in the reactor decreases, the heat resistance stability of the chlorinated polyethylene material increases. The present application injects an inactive gas into the reactor to continuously replace the oxygen in the reaction liquid and the gas phase on the upper surface of the reactor liquid, thereby reducing the oxygen content in the system, reducing the oxidation of high-density polyethylene during the chlorination process, improving the heat resistance stability of chlorinated polyethylene products, and meeting the high-temperature processing requirements of polyester materials.

[0045] In one embodiment, the inert gas is nitrogen or an inert gas, preferably nitrogen.

[0046] In the present application, the dispersants and emulsifiers mentioned can be conventional reagents in the art without special restrictions. For example, the dispersants used may include water-soluble alkyl acrylate polymer dispersants, maleic acid (ester) alkyl ester polymer dispersants, etc., wherein the alkyl group is preferably C1-C 12 The alkyl group may be a C1-C5 alkyl group, a C1-C3 alkyl group. For example, sodium (meth)acrylate-methyl methacrylate copolymer, sodium maleate-methyl methacrylate copolymer, etc. The emulsifier used is, for example, a nonionic emulsifier, including, for example, polyol esters or alkylphenol polyoxyethylene ethers. For example, the emulsifier used may include polyoxyethylene lauryl ether, fatty alcohol polyoxyethylene ether, nonylphenol polyoxyethylene ether, etc.

[0047] In the present invention, the lower limit of the glass transition temperature of the chlorinated polyethylene is not particularly limited. In some embodiments, for example, the glass transition temperature of the chlorinated polyethylene may be greater than -200°C, or greater than -100°C, or greater than -60°C, etc.

[0048] In a preferred embodiment, in step 3), the temperature of each section of the twin-screw extruder is set as follows: barrel temperature 85-130°C, confluence core temperature 80-100°C, and mold temperature 85-110°C.

[0049] In a third aspect, the present invention further provides a modified polyester, wherein the modified polyester is a polyester modified by using the above-mentioned toughening modifier.

[0050] In one embodiment, the modified polyester is prepared from raw materials comprising the following components in parts by weight: 100 parts by weight of the polyester, 5 to 12 parts by weight of the toughening modifier, and 75 to 150 parts by weight of filler. In the present invention, the toughening modifier is as described above.

[0051] In one embodiment, the filler is selected from one or more of calcium carbonate, talc, titanium dioxide, calcium oxide, and silicon dioxide. In some embodiments, the filler and the filler may be the same or different.

[0052] In the present invention, the polyester is not particularly limited, and any commonly used polyester can be used in the present invention. For example, the polyester used can include polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene terephthalate-1,4-cyclohexanedimethanol ester (PETG), polyethylene-2,6-naphthalate (PEN), polytrimethylene terephthalate (PTT) and other materials.

[0053] In a fourth aspect, the present invention also provides a method for preparing the modified polyester, comprising the following steps: weighing 100 parts by weight of the polyester, 5 to 12 parts by weight of the toughening modifier, and 75 to 150 parts by weight of an inorganic filler, stirring and mixing, and extruding through a twin-screw extruder.

[0054] In one embodiment, the barrel temperature of the twin-screw extruder is 180-265°C, and the die temperature is 195-260°C.

[0055] In the present application, in order to prevent the toughening modifier used for toughening modification from thermally decomposing during the processing of the polyester material, the thermal decomposition temperature of the toughening modifier is greater than the processing temperature of the polyester. For example, when the polyester material is processed in a twin-screw extruder, the processing temperature covers the extrusion temperature of the polyester, and in this case, the thermal decomposition temperature of the toughening modifier needs to be greater than the extrusion temperature.

[0056] In addition, since different polyesters may have the same or different processing temperatures, in order to prevent the toughening modifier from thermally decomposing during the processing of the polyester material, a suitable toughening modifier may be selected according to the polyester. For example, when the polyester is PETG, the thermal decomposition temperature of the toughening modifier is preferably greater than 200°C; when the polyester is PET, the thermal decomposition temperature of the toughening modifier is preferably greater than 245°C.

[0057] Hereinafter, the present application will be further described in conjunction with embodiments.

[0058] <Source of raw materials>

[0059] PET: China Resources Chemical Materials Technology Co., Ltd. (CR8816)

[0060] PETG: China Resources Chemical Materials Technology Co., Ltd. (CR5511)

[0061] High-density polyethylene: Nanjing Yangzi Petrochemical Co., Ltd. (2080)

[0062] DCP: Anhui Hengqi New Materials Co., Ltd.

[0063] BIBP: Wuhan Kangqiong Biopharmaceutical Technology Co., Ltd.

[0064] Glycidyl Methacrylate: Guangzhou Sanwang Chemical Materials Co., Ltd.

[0065] Calcium carbonate: Qingzhou Yuxin Calcium Industry Co., Ltd. (light calcium carbonate, 1250 mesh)

[0066] Calcium zinc stabilizer: Jiangsu Lianmeng Chemical Co., Ltd. (IF-S8003-4)

[0067] Organic tin stabilizer: Yunnan Tin Industry Tin Chemical Materials Co., Ltd. Suzhou Branch (TY-181)

[0068] Hydrotalcite: Tianjin Jinheng Blue Ocean Technology Co., Ltd.

[0069] Methyl methacrylate / acrylic acid copolymer: Shandong Riko Chemical Co., Ltd. (HL-FS)

[0070] Polyoxyethylene lauryl ether: Sanjiang Chemical Co., Ltd.

[0071] <Test Method>

[0072] Glass transition temperature: refer to the differential scanning calorimetry method of national standard GB / T 19466.2-2004.

[0073] Residual crystallinity: The heat of fusion was determined by differential scanning calorimetry according to the national standard GB / T 19466.3-2004, and the residual crystallinity was calculated according to the following formula:

[0074] Residual crystallinity = fusion heat of chlorinated polyethylene / theoretical fusion heat of HDPE with 100% crystallinity; the unit of fusion heat is kJ / kg.

[0075] Impact strength: Refer to national standard GB / T 1043.1-2008.

[0076] Chlorine content: Refer to the national standard GB / T 7139-2002 method B combustion bottle method.

[0077] Thermal decomposition temperature: Turn on the constant temperature oil bath heating and stirrer, and heat to 80℃. Put the sample into the glass test tube to the 10ml mark. Put the Congo red test paper roll into the glass test tube, put it into the cuvette together with the rubber stopper, and put the cuvette into the constant temperature oil bath. Increase the temperature at a rate of 2℃ per minute, and record the temperature at which the Congo red test paper changes color.

[0078] Reaction conversion rate = (weight of generated chlorinated polyethylene powder / weight of feed reactant) × 100%; when chlorine is the reactant, the amount of chlorine is calculated as half of the actual amount added.

[0079] Specifications of the extruder: Parallel twin screws: screw diameter = 114 mm, aspect ratio (L / D) = 28, main engine speed = 50 rpm.

[0080] Example 1

[0081] In a reactor equipped with a stirring paddle, 0.05 parts by weight of methyl methacrylate / acrylic acid copolymer soluble in water is added as a dispersant, 0.005 parts by weight of polyoxyethylene lauryl ether is added as an emulsifier, and then an appropriate amount of water is added to make the total amount of dispersant, emulsifier and water 150 parts by weight, and then 20 parts by weight of high-density polyethylene is added, stirring and heating are turned on, nitrogen is passed from the bottom of the reactor for 20 minutes, and after heating to 105°C under stirring, 3.5 parts by weight of chlorine are started, and the speed of chlorine is maintained at 0.05 parts by weight / min, and then the temperature is raised to 120°C while passing chlorine, and the heating and chlorine are carried out simultaneously. After the chlorine is passed, it is cooled to 95°C. The acid water of the obtained reactant was filtered out through a filter bag for deacidification, neutralization, water washing, centrifugation and drying to obtain a chlorinated polyethylene powder with a chlorine content of 8.0wt%, a glass transition temperature of -44.6°C, a residual crystallinity of 13.8% and a thermal decomposition temperature of 274°C (referred to as chlorinated polyethylene powder 1).

[0082] Preparation of toughening modifier:

[0083] The chlorinated polyethylene powder 1 is used to prepare a toughening modifier, and the specific ratio is: chlorinated polyethylene powder 1: 93.8 parts by weight; glycidyl methacrylate: 5.0 parts by weight, dicumyl peroxide: 0.2 parts by weight, light calcium carbonate: 0.5 parts by weight, and organic tin stabilizer: 0.5 parts by weight. The weights are weighed according to the above ratios.

[0084] Put the weighed materials into the mixing equipment in the order of chlorinated polyethylene powder, glycidyl methacrylate, dicumyl peroxide, stabilizer and light calcium carbonate, start stirring and mix at room temperature for 3 minutes. Put the materials aside for later use.

[0085] The mixed materials are extruded and granulated in a parallel twin-screw device. The specific extrusion granulation process conditions are shown in Table 1:

[0086] Table 1: Extrusion granulation process conditions

[0087]

[0088]

[0089] The extruded material was pelletized by a pelletizer to obtain toughening modifier sample 1, and the thermal decomposition temperature was measured to be 286°C.

[0090] Example 2

[0091] In a reactor equipped with a stirring paddle, 0.45 parts by weight of methyl methacrylate / acrylic acid copolymer soluble in water was added as a dispersant, 0.05 parts by weight of polyoxyethylene lauryl ether was added as an emulsifier, and then an appropriate amount of water was added to make the total amount of dispersant, emulsifier and water 150 parts by weight, and then 30 parts by weight of high-density polyethylene was added, stirring and heating were turned on, nitrogen was passed from the bottom of the reactor for 20 minutes, and after heating to 90°C under stirring, 20 parts by weight of chlorine was started, and the speed of chlorine was maintained at 0.1 parts by weight / min, and then the temperature was raised to 136°C while passing chlorine, and the heating and chlorine were carried out simultaneously. After the chlorine was passed, it was cooled to 98°C. The acid water of the obtained reactant was filtered out through a filter bag for deacidification, neutralization, water washing, centrifugation and drying to obtain a chlorinated polyethylene powder (chlorinated polyethylene powder 2) with a chlorine content of 25.0wt%, a glass transition temperature of -21.2°C, a residual crystallinity of 2.2% and a thermal decomposition temperature of 198°C.

[0092] Preparation of toughening modifier:

[0093] The chlorinated polyethylene powder 2 is used to prepare a toughening modifier, and the specific ratio is: chlorinated polyethylene powder 2: 93.488 parts by weight; glycidyl methacrylate: 1.0 parts by weight, di-tert-butyl peroxide isopropylbenzene: 0.012 parts by weight, silicon dioxide: 5.0 parts by weight, and hydrotalcite: 0.5 parts by weight. The above ratios are weighed.

[0094] The extrusion process was carried out according to Example 1.

[0095] The extruded material was pelletized by a pelletizer to obtain toughening modifier sample 2, and the thermal decomposition temperature was measured to be 204°C.

[0096] Example 3

[0097] In a reactor equipped with a stirring paddle, 0.26 parts by weight of methyl methacrylate / acrylic acid copolymer soluble in water was added as a dispersant, 0.03 parts by weight of polyoxyethylene lauryl ether was added as an emulsifier, and then an appropriate amount of water was added to make the total amount of dispersant, emulsifier and water 150 parts by weight, and then 24 parts by weight of high-density polyethylene was added, stirring and heating were turned on, nitrogen was introduced from the bottom of the reactor for 20 minutes, and after heating to 96°C under stirring, 10 parts by weight of chlorine was introduced, and the speed of chlorine was maintained at 0.08 parts by weight / min, and then the temperature was raised to 132°C while chlorine was passed, and the heating and chlorine were carried out simultaneously. After the chlorine was passed, it was cooled to 95°C. The acid water of the obtained reactant was filtered out through a filter bag for deacidification, neutralization, water washing, centrifugation and drying to obtain a chlorinated polyethylene powder (chlorinated polyethylene powder 3) with a chlorine content of 17.2wt%, a glass transition temperature of -33.9°C, a residual crystallinity of 7.4% and a thermal decomposition temperature of 257°C.

[0098] Preparation of toughening modifier:

[0099] The chlorinated polyethylene powder 3 is used to prepare a toughening modifier, and the specific ratio is: chlorinated polyethylene powder 3: 93.48 parts by weight; glycidyl methacrylate: 3.0 parts by weight, dicumyl peroxide: 0.02 parts by weight, light calcium carbonate: 3.0 parts by weight, and hydrotalcite: 0.5 parts by weight. The weights are weighed according to the above ratios.

[0100] The extrusion process was carried out according to Example 1.

[0101] The extruded material was pelletized by a pelletizer to obtain toughening modifier sample 3, and the thermal decomposition temperature was measured to be 264°C.

[0102] Comparative Example 1

[0103] In a reactor equipped with a stirring paddle, 0.28 parts by weight of methyl methacrylate / acrylic acid copolymer soluble in water is added as a dispersant, 0.062 parts by weight of polyoxyethylene lauryl ether is added as an emulsifier, and then an appropriate amount of water is added to make the total amount of dispersant, emulsifier and water 150 parts by weight, and then 30 parts by weight of high-density polyethylene is added, stirring and heating are turned on, nitrogen is passed from the bottom of the reactor for 20 minutes, and after heating to 80°C under stirring, 32.3 parts by weight of chlorine are started, and the speed of chlorine is maintained at 0.2 parts by weight / min, and then the temperature is raised to 132°C while passing chlorine, and the heating and chlorine are carried out simultaneously. After the chlorine is passed, it is cooled to 100°C. The acid water of the obtained reactant was filtered out through a filter bag for deacidification, neutralization, water washing, centrifugation and drying to obtain a chlorinated polyethylene powder (chlorinated polyethylene powder 4) with a chlorine content of 35.0wt%, a glass transition temperature of -9.4°C, a residual crystallinity of 0.2% and a thermal decomposition temperature of 170°C.

[0104] Preparation of toughening modifier:

[0105] The chlorinated polyethylene powder 4 is used to prepare a toughening modifier, and the specific ratio is: chlorinated polyethylene powder 4: 93.48 parts by weight; glycidyl methacrylate: 3.0 parts by weight, dicumyl peroxide: 0.02 parts by weight, light calcium carbonate: 3.0 parts by weight, and hydrotalcite: 0.5 parts by weight. The weights are weighed according to the above ratios.

[0106] The processing was carried out by referring to the extrusion process of Example 1. The extruded material was pelletized by a pelletizer to obtain toughening modifier sample 4, and the thermal decomposition temperature was measured to be 174°C.

[0107] Comparative Example 2

[0108] In a reactor equipped with a stirring paddle, 0.45 parts by weight of methyl methacrylate / acrylic acid copolymer soluble in water is added as a dispersant, 0.05 parts by weight of polyoxyethylene lauryl ether is added as an emulsifier, and then an appropriate amount of water is added to make the total amount of dispersant, emulsifier and water 150 parts by weight, and then 30 parts by weight of high-density polyethylene is added, stirring and heating are turned on, and after heating to 90°C under stirring, 20 parts by weight of chlorine are started to be passed, and the speed of passing chlorine is maintained at 0.1 parts by weight / min, and then the temperature is raised to 136°C while passing chlorine, and the heating and passing chlorine are carried out simultaneously. After the chlorine is passed, it is cooled to 98°C. The acid water of the obtained reactant is filtered out by a filter bag for deacidification, neutralized, washed, centrifuged, and dried to obtain a chlorine content of 25.0wt%, a glass transition temperature of -21.0°C, a residual crystallinity of 2.1%, and a chlorinated polyethylene powder (chlorinated polyethylene powder 5) with a thermal decomposition temperature of 187°C.

[0109] Preparation of toughening modifier:

[0110] The chlorinated polyethylene powder 5 is used to prepare a toughening modifier, and the specific ratio is: chlorinated polyethylene powder 5: 93.488 parts by weight; glycidyl methacrylate: 1.0 parts by weight, dicumyl peroxide: 0.012 parts by weight, light calcium carbonate: 5.0 parts by weight, and hydrotalcite: 0.5 parts by weight. The above ratios are weighed.

[0111] The processing was carried out by referring to the extrusion process of Example 1. The extruded material was pelletized by a pelletizer to obtain toughening modifier sample 5, and the thermal decomposition temperature was measured to be 193°C.

[0112] The thermal decomposition temperature of the toughening modifiers prepared in Examples 1-3 and Comparative Examples 1-2 was tested. It can be seen that as the chlorine content decreases, the thermal decomposition temperature of the product increases. At the same time, in the preparation process of chlorinated polyethylene, the oxygen in the reaction container is replaced by nitrogen, which can improve the thermal stability. It can be seen from the examples and comparative examples that in the preparation process of the toughening modifier, the thermal decomposition temperature of the chlorinated polyethylene powder increases under the action of the stabilizer, and the stability is improved to a certain extent.

[0113] The toughening modifiers prepared in Examples 1-3 and the toughening modifiers prepared in Comparative Examples 1-2 were applied to specific polyester materials, and their toughening modification effects on the polyester materials were compared as shown in Table 2.

[0114] Table 2: Performance test of toughening modifier samples 1-5

[0115]

[0116]

[0117] Through comparison, it was found that compared with polyester materials without adding any toughening modifiers, the addition of toughening modifiers will affect the impact properties of polyester materials. Among them, toughening modifiers with thermal decomposition temperatures higher than 200°C can significantly improve the impact properties of polyester materials, with an increase of more than 100%. However, toughening modifiers with thermal decomposition temperatures lower than the processing temperature of polyester materials do not improve the impact properties of polyester materials, but may reduce the impact properties.

[0118] According to the comparison of thermal decomposition temperature data of toughening modifiers, it can be seen that with the increase of chlorine content, the thermal decomposition temperature of the toughening agent gradually decreases; in addition, by reducing the oxygen content in the reactor and using stabilizer materials for modification, it can also help improve the thermal stability.

[0119] Example 4

[0120] In a reactor equipped with a stirring paddle, 0.08 parts by weight of methyl methacrylate / acrylic acid copolymer soluble in water was added as a dispersant, 0.01 parts by weight of polyoxyethylene lauryl ether was added as an emulsifier, and then an appropriate amount of water was added to make the total amount of dispersant, emulsifier and water 150 parts by weight, and then 22 parts by weight of high-density polyethylene was added, stirring and heating were turned on, nitrogen was passed from the bottom of the reactor for 20 minutes, and after heating to 102°C under stirring, 6 parts by weight of chlorine was started, and the speed of chlorine was maintained at 0.06 parts by weight / min, and then the temperature was raised to 130°C while passing chlorine, and the heating and chlorine were carried out simultaneously. After the chlorine was passed, it was cooled to 98°C. The acid water of the obtained reactant was filtered out through a filter bag for deacidification, neutralization, water washing, centrifugation and drying to obtain a chlorinated polyethylene powder (chlorinated polyethylene powder 6) with a chlorine content of 12.0wt%, a glass transition temperature of -40.8°C, a residual crystallinity of 12.3% and a thermal decomposition temperature of 268°C.

[0121] Preparation of toughening modifier:

[0122] The chlorinated polyethylene powder 6 is used to prepare a toughening modifier, and the specific ratio is: chlorinated polyethylene powder 6: 94.49 parts by weight; glycidyl methacrylate: 1.5 parts by weight, dicumyl peroxide: 0.01 parts by weight, talc: 3.0 parts by weight, and hydrotalcite: 1.0 parts by weight. The weights are weighed according to the above ratios.

[0123] The processing was carried out in accordance with the extrusion process of Example 1. The extruded material was pelletized by a pelletizer to obtain a toughening modifier sample 6, and the thermal decomposition temperature was measured to be 273°C.

[0124] Example 5

[0125] The chlorinated polyethylene powder 6 prepared in Example 4 was used to prepare a toughening modifier, and the specific ratio was: chlorinated polyethylene powder 6: 92.98 parts by weight; glycidyl methacrylate: 3.0 parts by weight, dicumyl peroxide: 0.02 parts by weight, talc: 3.0 parts by weight, and hydrotalcite: 1.0 parts by weight. The above ratios were weighed.

[0126] The processing was carried out in accordance with the extrusion process of Example 1. The extruded material was pelletized by a pelletizer to obtain a toughening modifier sample 7, and the thermal decomposition temperature was measured to be 275°C.

[0127] Example 6

[0128] The chlorinated polyethylene powder 6 prepared in Example 4 was used to prepare a toughening modifier, and the specific ratio was: chlorinated polyethylene powder 6: 91.47 parts by weight; glycidyl methacrylate: 4.5 parts by weight, dicumyl peroxide: 0.03 parts by weight, talc: 3.0 parts by weight, and hydrotalcite: 1.0 parts by weight. The weights were weighed according to the above ratios.

[0129] The processing was carried out by referring to the extrusion process of Example 1. The extruded material was pelletized by a pelletizer to obtain toughening modifier sample 8, and the thermal decomposition temperature was measured to be 274°C.

[0130] Example 7

[0131] In a reactor equipped with a stirring paddle, 0.1 parts by weight of methyl methacrylate / acrylic acid copolymer soluble in water was added as a dispersant, 0.015 parts by weight of polyoxyethylene lauryl ether was added as an emulsifier, and then an appropriate amount of water was added to make the total amount of dispersant, emulsifier and water 150 parts by weight, and then 27.5 parts by weight of high-density polyethylene was added, stirring and heating were turned on, nitrogen was passed from the bottom of the reactor for 20 minutes, and after heating to 90°C under stirring, 9.7 parts by weight of chlorine was started, and the speed of chlorine was maintained at 0.075 parts by weight / min, and then the temperature was raised to 134°C while passing chlorine, and the heating and chlorine were carried out simultaneously. After the chlorine was passed, it was cooled to 95°C. The acid water of the obtained reactant was filtered out through a filter bag for deacidification, neutralization, water washing, centrifugation and drying to obtain a chlorinated polyethylene powder (chlorinated polyethylene powder 7) with a chlorine content of 15.0wt%, a glass transition temperature of -35.0°C, a residual crystallinity of 9.7% and a thermal decomposition temperature of 264°C.

[0132] Preparation of toughening modifier:

[0133] The chlorinated polyethylene powder 7 is used to prepare a toughening modifier, and the specific ratio is: chlorinated polyethylene powder 7: 91.576 parts by weight; glycidyl methacrylate: 3.0 parts by weight, dicumyl peroxide: 0.024 parts by weight, calcium oxide: 1.5 parts by weight, and calcium zinc stabilizer: 4.0 parts by weight. The above ratios are weighed.

[0134] The processing was carried out by referring to the extrusion process of Example 1. The extruded material was pelletized by a pelletizer to obtain a toughening modifier sample 9, and the thermal decomposition temperature was measured to be 272°C.

[0135] Comparative Example 3

[0136] In a reactor equipped with a stirring paddle, 0.05 parts by weight of methyl methacrylate / acrylic acid copolymer soluble in water was added as a dispersant, 0.005 parts by weight of polyoxyethylene lauryl ether was added as an emulsifier, and then an appropriate amount of water was added to make the total amount of dispersant, emulsifier and water 150 parts by weight, and then 20 parts by weight of high-density polyethylene was added, stirring and heating were turned on, nitrogen was introduced from the bottom of the reactor for 20 minutes, and after heating to 80°C under stirring, 3.5 parts by weight of chlorine was introduced, and the speed of chlorine was maintained at 0.05 parts by weight / min, and then the temperature was raised to 115°C while chlorine was passed, and the heating and chlorine were carried out simultaneously. After the chlorine was passed, it was cooled to 98°C. The acid water of the obtained reactant was filtered out through a filter bag for deacidification, neutralization, water washing, centrifugation and drying to obtain a chlorinated polyethylene powder (chlorinated polyethylene powder 8) with a chlorine content of 8.0wt%, a glass transition temperature of -46.6°C, a residual crystallinity of 22.4% and a thermal decomposition temperature of 271°C.

[0137] Preparation of toughening modifier:

[0138] The chlorinated polyethylene powder 8 is used to prepare a toughening modifier, and the specific ratio is: chlorinated polyethylene powder 8: 93.8 parts by weight; glycidyl methacrylate: 5.0 parts by weight, dicumyl peroxide: 0.2 parts by weight, light calcium carbonate: 0.5 parts by weight, and organic tin stabilizer: 0.5 parts by weight. The above ratios are weighed.

[0139] The processing was carried out in accordance with the extrusion process of Example 1. The extruded material was pelletized by a pelletizer to obtain a toughening modifier sample 10, and the thermal decomposition temperature was measured to be 273°C.

[0140] Comparative Example 4

[0141] Preparation of toughening modifier:

[0142] The chlorinated polyethylene powder 1 is used to prepare a toughening modifier, and the specific ratio is: chlorinated polyethylene powder 1: 99.0 parts by weight; light calcium carbonate: 0.5 parts by weight, and organic tin stabilizer: 0.5 parts by weight. The weights are weighed according to the above ratios.

[0143] The processing was carried out by referring to the extrusion process of Example 1. The extruded material was pelletized by a pelletizer to obtain a toughening modifier sample 11, and the thermal decomposition temperature was measured to be 284°C.

[0144] Comparative Example 5

[0145] In a reactor equipped with a stirring paddle, 0.045 parts by weight of methyl methacrylate / acrylic acid copolymer soluble in water was added as a dispersant, 0.005 parts by weight of polyoxyethylene lauryl ether was added as an emulsifier, and then an appropriate amount of water was added to make the total amount of dispersant, emulsifier and water 150 parts by weight, and then 20 parts by weight of high-density polyethylene was added, stirring and heating were turned on, nitrogen was introduced from the bottom of the reactor for 20 minutes, and after heating to 108°C under stirring, 3 parts by weight of chlorine was introduced, and the speed of chlorine was maintained at 0.05 parts by weight / min, and then the temperature was raised to 130°C while chlorine was passed, and the heating and chlorine were carried out simultaneously. After the chlorine was passed, it was cooled to 98°C. The acid water of the obtained reactant was filtered out through a filter bag for deacidification, neutralization, water washing, centrifugation and drying to obtain a chlorinated polyethylene powder (chlorinated polyethylene powder 9) with a chlorine content of 7.0wt%, a glass transition temperature of -48.6°C, a residual crystallinity of 30.4% and a thermal decomposition temperature of 279°C.

[0146] Preparation of toughening modifier:

[0147] The chlorinated polyethylene powder 9 is used to prepare a toughening modifier, and the specific ratio is: chlorinated polyethylene powder 9: 93.8 parts by weight; glycidyl methacrylate: 5.0 parts by weight, dicumyl peroxide: 0.2 parts by weight, light calcium carbonate: 0.5 parts by weight, and organic tin stabilizer: 0.5 parts by weight. The weights are weighed according to the above ratios.

[0148] The processing was carried out in accordance with the extrusion process of Example 1. The extruded material was pelletized by a pelletizer to obtain a toughening modifier sample 12, and the thermal decomposition temperature was measured to be 292°C.

[0149] The toughening modifiers prepared in Examples 1, 4-7 and the toughening modifiers prepared in Comparative Examples 3-5 were applied to specific polyester materials, and their toughening modification effects on the polyester materials were compared as shown in Table 3.

[0150] Table 3: Performance test of toughening modifier samples No. 1, 6-12

[0151]

[0152]

[0153] Analysis of the test data shows that, by comparing 2-1#, 2-6# and 2-8#, it can be seen that with the increase of residual crystallinity, the impact strength of the toughening modifier modified polyester material gradually decreases. By comparing the test results of 2-2#, 2-3# and 2-4# and 2-1# and 2-7#, it can be seen that with the increase of the amount of grafted glycidyl methacrylate, the impact strength of the toughening modifier modified polyester material gradually increases. Combining the above data, it can be inferred that polyethylene is a non-polar material and has poor compatibility with polyester materials. Chlorination or grafting of glycidyl methacrylate is conducive to the compatibility of chlorinated polyethylene with polyester resin and improves its toughening effect.

[0154] Example 8

[0155] In a reactor equipped with a stirring paddle, 0.3 parts by weight of methyl methacrylate / acrylic acid copolymer soluble in water was added as a dispersant, 0.036 parts by weight of polyoxyethylene lauryl ether was added as an emulsifier, and then an appropriate amount of water was added to make the total amount of dispersant, emulsifier and water 150 parts by weight, and then 27.5 parts by weight of high-density polyethylene was added, stirring and heating were turned on, nitrogen was passed from the bottom of the reactor for 20 minutes, and after heating to 94°C under stirring, 13.75 parts by weight of chlorine was started, and the speed of chlorine was maintained at 0.08 parts by weight / min, and then the temperature was raised to 135°C while passing chlorine, and the heating and chlorine were carried out simultaneously. After the chlorine was passed, it was cooled to 96°C. The acid water of the obtained reactant was filtered out through a filter bag for deacidification, neutralization, water washing, centrifugation and drying to obtain a chlorinated polyethylene powder (chlorinated polyethylene powder 10) with a chlorine content of 20.0wt%, a glass transition temperature of -28.0°C, a residual crystallinity of 4.6% and a thermal decomposition temperature of 230°C.

[0156] Preparation of toughening modifier:

[0157] The chlorinated polyethylene powder 10 is used to prepare a toughening modifier, and the specific ratio is: chlorinated polyethylene powder 10: 93.48 parts by weight; glycidyl methacrylate: 3.0 parts by weight, dicumyl peroxide: 0.02 parts by weight, light calcium carbonate: 3.0 parts by weight, and zeolite: 0.5 parts by weight. The weights are weighed according to the above ratios.

[0158] The processing was carried out in accordance with the extrusion process of Example 1. The extruded material was pelletized by a pelletizer to obtain a toughening modifier sample 13, and the thermal decomposition temperature was measured to be 241°C.

[0159] Example 9

[0160] The chlorinated polyethylene powder 1 is used to prepare a toughening modifier, and the specific ratio is: chlorinated polyethylene powder 1: 93.48 parts by weight; glycidyl methacrylate: 3.0 parts by weight, dicumyl peroxide: 0.02 parts by weight, talc: 3.0 parts by weight, and hydrotalcite: 0.5 parts by weight. The weights are weighed according to the above ratios.

[0161] The processing was carried out in accordance with the extrusion process of Example 1. The extruded material was pelletized by a pelletizer to obtain a toughening modifier sample 14, and the thermal decomposition temperature was measured to be 284°C.

[0162] Example 10

[0163] The chlorinated polyethylene powder 3 is used to prepare a toughening modifier, and the specific ratio is: chlorinated polyethylene powder 1: 93.48 parts by weight; glycidyl methacrylate: 3.0 parts by weight, dicumyl peroxide: 0.02 parts by weight, talc: 3.0 parts by weight, and hydrotalcite: 0.5 parts by weight. The weights are weighed according to the above ratios.

[0164] The processing was carried out in accordance with the extrusion process of Example 1. The extruded material was pelletized by a pelletizer to obtain a toughening modifier sample 15, and the thermal decomposition temperature was measured to be 205°C.

[0165] The relationship between the chlorine content and glass transition temperature of different chlorinated polyethylene powders is shown in Table 4:

[0166] Table 4: Relationship between chlorine content and glass transition temperature of different chlorinated polyethylene powders

[0167]

[0168]

[0169] The above toughening modifiers were added to polyester materials to compare the impact performance differences. See Table 5 for details.

[0170] Table 5: Performance test of toughening modifier samples with different chlorine contents

[0171]

[0172]

[0173] Analysis of the data in Tables 4 and 5 shows that as the chlorine content increases, the residual crystallinity of the chlorinated polyethylene material gradually decreases and the glass transition temperature gradually increases; through the analysis of the data in Table 3, when the chlorine content is the same, the reduction of residual crystallinity is beneficial to improving the impact performance. In Table 5, the impact strength of the polyester material modified by the toughening modifier shows a trend of first increasing and then decreasing, which is presumably the result of the dual effects of the residual crystallinity and glass transition temperature of the toughening modifier. That is, a low glass transition temperature is beneficial for the toughening modifier to give the polyester material good impact properties, but a low residual crystallinity is also beneficial for the toughening modifier to give the polyester material good impact properties. The toughening modifier needs to be controlled simultaneously in terms of residual crystallinity and glass transition temperature parameters.

Claims

1. A toughening modifier for polyester, characterized in that: The raw materials are prepared by comprising the following components in parts by weight: The chlorinated polyethylene has a chlorine content of 8 to 25 wt%, a glass transition temperature of <-20°C, and a residual crystallinity of 0≤<15%; The residual crystallinity is determined by the heat of fusion measured by differential scanning calorimetry according to the national standard GB / T 19466.3-2004 and calculated by the following formula: Residual crystallinity = fusion heat of chlorinated polyethylene / theoretical fusion heat of HDPE with 100% crystallinity; The thermal decomposition temperature of the toughening modifier is greater than 200°C; Preferably, the chlorine content of the chlorinated polyethylene is 8-18 wt %, and the thermal decomposition temperature of the toughening modifier is greater than 245°C.

2. The toughening modifier according to claim 1, characterized in that The compatibilizer is glycidyl methacrylate.

3. The toughening modifier according to claim 1 or 2, characterized in that: The initiator is selected from one or more of dicumyl peroxide, di-tert-butylcumyl peroxide, benzoyl peroxide, and dicumyl hydroperoxide.

4. The toughening modifier according to claim 1 or 2, characterized in that: The filler is selected from one or more of calcium carbonate, talc, titanium dioxide, calcium oxide and silicon dioxide.

5. The toughening modifier according to claim 1 or 2, characterized in that: The stabilizer is one or more of an organic tin stabilizer, a calcium zinc composite stabilizer, a lead salt composite stabilizer, hydrotalcite, and a zeolite.

6. A method for preparing the toughening modifier according to any one of claims 1 to 5, characterized in that: The steps include: Step 1): adding 0.05-0.5 parts by weight of a dispersant and 0.005-0.06 parts by weight of an emulsifier to a reactor, then adding water to make the total weight of the dispersant, the emulsifier and the water 150 parts by weight, then adding 20-30 parts by weight of high-density polyethylene, introducing an inactive gas from the bottom of the reactor to remove oxygen in the reaction liquid and the gas phase at the top of the reactor, heating the reaction mass to 80-105° C. under stirring, beginning to introduce 3.5-20 parts by weight of chlorine, and simultaneously raising the temperature to 120-140° C., after the chlorine is introduced, cooling to below 100° C., deacidification, neutralization, water washing, centrifugation, and drying to obtain chlorinated polyethylene with a chlorine content of 8-25wt%, a glass transition temperature of less than -20° C., and a residual crystallinity of 0≤less than 15%; Step 2): weigh 85.0-97.2 parts by weight of the chlorinated polyethylene, 0.8-5.0 parts by weight of the compatibilizer, 0.01-0.2 parts by weight of the initiator, 0.5-6.0 parts by weight of the filler, and 0.5-4.0 parts by weight of the stabilizer, put them into a mixer, stir and mix for 2-5 minutes, and discharge the materials for later use; Step 3): the mixed material is extruded and granulated through a twin-screw extruder to obtain the toughening modifier; Preferably, the inert gas is nitrogen or an inert gas, preferably nitrogen.

7. The method according to claim 6, characterized in that In step 3), the temperature of each section of the twin-screw extruder is set as follows: barrel temperature 85-130°C, confluence core temperature 80-100°C, and mold temperature 85-110°C.

8. A modified polyester, characterized in that: The modified polyester is a polyester modified by using a toughening modifier as described in any one of claims 1 to 5 or a toughening modifier prepared by the method as described in any one of claims 6 to 7.

9. The modified polyester according to claim 8, characterized in that The modified polyester is prepared by raw materials comprising the following components in parts by weight: 100 parts by weight of polyester; 5 to 12 parts by weight of the toughening modifier; Filler 75-150 parts by weight; The filler is selected from one or more of calcium carbonate, talc, titanium dioxide, calcium oxide, and silicon dioxide; Preferably, the polyester is selected from one or more of polyethylene terephthalate, polybutylene terephthalate, polyethylene terephthalate-1,4-cyclohexanedimethanol terephthalate, poly-2,6-naphthalene dicarboxylate, and polytrimethylene terephthalate.

10. A method for preparing the modified polyester according to claim 8 or 9, characterized in that: The method comprises the following steps: weighing 100 parts by weight of the polyester, 5 to 12 parts by weight of the toughening modifier, and 75 to 150 parts by weight of the filler, stirring and mixing, and extruding through a twin-screw extruder; The thermal decomposition temperature of the toughening modifier is greater than the extrusion temperature of the polyester, preferably the thermal decomposition temperature of the toughening modifier is greater than 200° C., more preferably the thermal decomposition temperature of the toughening modifier is greater than 245° C.; Preferably, the barrel temperature of the twin-screw extruder is 180-265°C, and the mold temperature is 195-260°C.

Citation Information

Patent Citations

  • Toughening plasticizing accelerant preparation method, product and application

    CN104004140A

  • Water-phase suspension preparation method for hard chlorinated polyethylene

    CN104829755A

  • APET (amorphous polyethylene terephthalate) toughened blister packaging material and preparation method thereof

    CN104962049A

  • Efficient plastic toughening agent

    CN110527234A

  • Thermoplastic resin composition

    US5281668A